От разграничения палатализованных и палатальных согласных к разграничению палатализаций и палатаций заднеязычных согласных в праславянском языке - Яковлевич Бурмистрович, Юрий (Slavistica Vilnensis, 2009)
The article explores two phonetic phenomena: palatation and palatalization. Taking into consideration the contribution made by V. Chekman and Kalleman toward the understanding of these phenomena, the article provides a thorough analysis of the processes and outcomes of the first, second, and third Common Slavic palatalizations of velar consonants.